Performance and emission assessment of an indirect ignition diesel engine fuelled with waste plastic pyrolysis oil and ethanol blends - Bhowmik, Mrinal; Deb, Madhujit; Sastry, G. R. K. (Frontiers in Thermal Engineering, 2025)
The present study examines the performance and emission attributes of an indirect injection diesel engine powered by blends of waste plastic pyrolysis oil (WPPO) and ethanol, evaluating their viability as substitutes for traditional diesel fuel. Experimental results reveal that blend BL2 (25 vol.% WPPO and 10 vol.% ethanol) exhibits superior brake thermal efficiency (BTHE), surpassing diesel by 1.3% at full load, while other prepared blends demonstrate comparable performance. Brake-specific fuel consumption decreases with increasing load, with BL2 outperforming diesel by 3.7% at full load. Unburned hydrocarbon emissions are lower for BL1 (15% WPPO and 5% ethanol) and BL2, with reductions of 6.7% and 10.4%, respectively, compared to diesel at full load. In contrast, blends with higher ethanol content show decreased nitric oxide emissions, with BL1 and BL2 reducing 20.1% and 21.7. Carbon monoxide emissions are consistently reduced across all blends, with 25% reductions attributed to improved oxygen availability for combustion. The findings demonstrate that WPPO-ethanol blends, particularly BL1 and BL2, offer a promising pathway for reducing environmental pollutants while maintaining or enhancing engine performance, highlighting their potential as supplementary fuels for internal combustion engines.